2010
DOI: 10.1002/casp.1057
|View full text |Cite
|
Sign up to set email alerts
|

Emotional display rules and emotion self‐regulation: Associations with bullying and victimization in community‐based after school programs

Abstract: We explored linkages among different components of emotional competence and bullying and victimization in children enrolled in community after school programs. Seventy-seven children were recruited from after school programs and their display rule knowledge for sadness and anger was evaluated. Their emotion self-regulation skills and bullying experiences were also assessed. Knowledge of display rules for sadness was a negative predictor of physical victimization whereas emotional lability/negativity was positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
1
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(70 citation statements)
references
References 64 publications
4
57
1
4
Order By: Relevance
“…[24][25][26][27] Most acts of aggression practiced in the school context under investigation were verbal, which suggests an apparent contradiction with the data related to sex, as boys are expected to engage more in physical attacks, while girls are expected to practice more verbal aggressions. 28 Nevertheless, this information may be interpreted in line with the proposals put forward in another Brazilian study 5 , which identified a prevalence of verbal aggressions independently from the aggressors' sex, as the school authorities generally interpret these as less serious and, therefore, less subject to severe punishment.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…[24][25][26][27] Most acts of aggression practiced in the school context under investigation were verbal, which suggests an apparent contradiction with the data related to sex, as boys are expected to engage more in physical attacks, while girls are expected to practice more verbal aggressions. 28 Nevertheless, this information may be interpreted in line with the proposals put forward in another Brazilian study 5 , which identified a prevalence of verbal aggressions independently from the aggressors' sex, as the school authorities generally interpret these as less serious and, therefore, less subject to severe punishment.…”
Section: Discussionmentioning
confidence: 67%
“…It also discourages the request for help to classmates, teachers or family members. 26 Demotivation, in turn, as a secondary emotion, influenced by social and cultural characteristics, emerges as a result of the existence of other primary emotions like sadness. It can influence the quality of the victims' relationships with colleagues and teachers, cause social isolation and impair the school performance.…”
Section: Discussionmentioning
confidence: 99%
“…Victims of bullying often exhibit difficulties in social understanding (Garner and Stowe Hinton 2010), occupy low social status (Card and Hodges 2007), and are perceived as 'different' or deviating from peer group norms (Horowitz et al 2004). The social experience of children with ASC reads remarkably similarly.…”
Section: What Is Bullying?mentioning
confidence: 99%
“…In fact, bullies usually motivate others against the target, and the identities of the perpetrators are often known to them [22]. Boys are more intimidated than girls while the family income appears to be negatively related to bullying [23]. It has been supported that the perception of bullying is significantly association with levels of shyness, the confidence and satisfaction with friendships [24].…”
Section: Introductionmentioning
confidence: 99%